The Impact Of Emotional Intelligence On Blood Sugar In Type 2 Diabetes Mellitus Patients - Ana Fitria Nusantara; Achmad Kusyairi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
People with type 2 diabetes mellitus have more risk of being depression ak perluthan non-diabetics, as evidenced by their poor or even low self-care. suffering from diabetes mellitus for long time can impact the emotional burden, in terms of diabetes treatment and the risk of complications. Diabetes-related stress associated with poor self-management behaviors (diet, physical activity, and medication adherence). The purpose of this study was to examine the relationship between emotional intelligence and blood sugar levels in people with type 2 diabetes mellitus using a descriptive analytical design with a cross-sectional approach. The sample was determined using a purposive sampling technique with 50 respondents. Researchers distributing questionnaires to measure emotional intelligence variables and observation sheets to measure blood sugar variables. The results showed that an average Emotional Intelligence score of 58.28 and an average blood sugar level of 235.91. The analysis showed a p-value of 0.001, indicating a significant relationship between emotional intelligence and blood glucose levels. Emotional Intelligence can influence self-management in diabetes sufferers, particularly in adhering to and implementing a diabetes management program.